2022
DOI: 10.1002/eom2.12184
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐assisted cooling to grow ultra‐stable Cs3Cu2l5 and CsCu2l3 single crystals for solid‐state lighting and visible light communication

Abstract: Owing to the excellent optical properties, white light‐emitting diodes (WLEDs) based on metal halide perovskites have attracted great attention as promising light source for solid‐state lighting and wireless visible light communication (VLC). However, the instability and toxicity of classic hybrid lead halides hinder their practical applications. Here, a pressure‐assisted cooling method is developed to grow lead‐free Cs3Cu2I5 and CsCu2I3 single crystals, which exhibit more excellent stability, larger size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…Single crystals with less grain boundaries, show advantages of improved carrier mobility, lower bulk defect state density, and more adequate light absorption. 48 Main techniques that were reported capable of synthesizing high performance single crystals include high-temperature Bridgeman ( Figure 5 A), heating precursor solution crystallization (inverse temperature crystallization, Figure 5 B), cooling precursor solution crystallization ( Figure 5 C), hot process ( Figure 5 D), 49 , 50 , 51 , 52 solvent volatilization, anti-solvent-assisted crystallization, vapor phase epitaxial growth, space-limited crystallization, cavitation triggered asymmetrical crystallization methods. For example, Chung et al.…”
Section: Basic Of Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Single crystals with less grain boundaries, show advantages of improved carrier mobility, lower bulk defect state density, and more adequate light absorption. 48 Main techniques that were reported capable of synthesizing high performance single crystals include high-temperature Bridgeman ( Figure 5 A), heating precursor solution crystallization (inverse temperature crystallization, Figure 5 B), cooling precursor solution crystallization ( Figure 5 C), hot process ( Figure 5 D), 49 , 50 , 51 , 52 solvent volatilization, anti-solvent-assisted crystallization, vapor phase epitaxial growth, space-limited crystallization, cavitation triggered asymmetrical crystallization methods. For example, Chung et al.…”
Section: Basic Of Perovskitesmentioning
confidence: 99%
“…dissolved the precursor at 100 °C and then lowered the temperature of the saturated precursor to room temperature at a rate of 1 °C h -1 to obtain cesium-copper-iodine single crystals with a centimeter scale. 51 However, the above-mentioned methods generally result in single crystals with a large size/thickness, limiting their applications in flexible X-ray detections. To solve such an issue, Zhang et al.…”
Section: Basic Of Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Also, Baiqian Wang et al developed a pressure-assisted cooling method to synthesize similar perovskites, which exhibit excellent stability for WLED and wireless visible light communication applications. 21 Qionghua Mo et al reported a newly developed air-stable hybrid lead-free halide like [Na (DMSO) 2 ] 3 SbBr 6 , which exhibits high photoluminescence quantum yield and long-term PL decay of 3.1 μs, and such a material is useful for next-generation solid-state illuminations and optoelectronic applications. 22 Furthermore, they improve the photoluminescence quantum yield and stability by incorporating Cl and varying the concentration of Sb in the same perovskites; thus, such work gives an insight into the development of Sb-based organic–inorganic metal halides for solid-state illumination and X-ray imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[33] In addition, Cs 3 Cu 2 I 5 displayed a broad emission band with a large Stokes shift, which are characteristics of STEs that are primarily seen in Cu(I)-based fluorescence. Following the initial Cs 3 Cu 2 I 5 study, analogs such as CsCu 2 X 3 and Cs 3 Cu 2 X 5 (X = Cl, Br, I) were synthesized, both in the bulk and as nanocrystals (NCs), [34][35][36][37][38][39][40][41][42] and in-depth analyses of their photophysical properties [43] -as well as studies on various applications, from scintillators to light-emitting diodes [44][45][46] were also carried out.…”
Section: Introductionmentioning
confidence: 99%